The Effect of Story Box Media-Assisted Inquiry Learning Model on the Ability to Complete Mathematical Story Questions - Diah Ayu Wahyuningrum (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the story box media assisted inquirylearning model on the ability to solve math story problems in grade 5 students of SDN 2 Kupen Pringsurat. This type of research is a pre-experiment with the One Group Pretest-Posttest Design model. The research subjects were taken by saturated sampling. The samples taken were 28 students. The data collection method was carried out by multiplechoice tests totaling 22 questions. The validity test uses the Pearson formula, thereliability test uses the Cronbach's alpha formula, the difficulty index test, thedistinguishing power test with the help of IBM SPSS Statistics 23.0 for windows . Theanalysis prerequisite test consisted of the Saphiro Wilk normality test with the helpof IBM SPSS Statistics 23.0 for windows. Data analysis used parametric statisticaltechniques, namely assisted Paired Sample T-test IBM SPSS Statistics 23.0 for windows .The results showed that the story box assisted inquiry model had a positive effect on theability to solve math story problems. This is evidenced by the results of the analysis ofthe Paired Sample T-test with a probability sig. (2-tailed) of 0.001 <0.05, with anaverage pre-test score of 53.14 and a post-test score of 79.86 . Based on the results of the analysis and discussion, there was an increase of 26.72 from the average score of the pre-test and post-test . The results of this study can be concluded that the inquiry learning model assisted by the story box media has a positive effect on the ability to solve mathstory problems.